Functional fermented sausages incorporated with microencapsulated Lactobacillus plantarum BG 112 in Acrycoat S100 - Vasconcelos, Lia (2021)
Microencapsulation is a promising alternative to ensure probiotic viability, mainly when the wall material resists the adverse extrinsic conditions releasing the probiotics into the intestine. Therefore, Lactobacillus plantarum was encapsulated in Acrycoat S100 by spray drying. The encapsulation process was analysed using a central composite rotatable design (CCRD), varying the encapsulant and probiotic microorganism concentrations to evaluate the microcapsule yield and encapsulation efficiency (EE). L. plantarum microcapsules added to a Milano-type salami formulation for a probiotic product were characterised by physicochemical and morphological analysis, and compared to a control. CCRD central points (5% encapsulant and 1% probiotic) showed the highest yield (above 35%) and EE (above 78%) values. The optimum microcapsule formulation was obtained with 5.57% encapsulant and 1% probiotic, achieving 80.9% EE. FTIR-ATR and thermal analysis showed efficient microorganisms entrapment in the microcapsules, increasing their thermal stability in optimised assays. Milano-type probiotic salami was obtained with 8 log CFU g-1 LAB counts. Physicochemical and sensory properties did not differ for salami formulations and ensured their good acceptance, demonstrating pH-dependent controlled release advantages compared to a usual probiotic product.